1996
DOI: 10.1210/endo.137.5.8612565
|View full text |Cite
|
Sign up to set email alerts
|

The third cytoplasmic domain of the GLP-1[7-36 amide] receptor is required for coupling to the adenylyl cyclase system.

Abstract: Truncated forms of glucagon-like peptide-1 (tGLP-1) are potent endogenous stimuli of insulin secretion from pancreatic beta cells and have powerful antidiabetogenic effects. In the present study we sought to determine the precise regions of the tGLP-1 receptor (R) that are required for its efficient coupling to the adenylyl cyclase (AC) system since it is well established that cAMP is the primary second messenger activated by tGLP-1. The predicted third intracellular loop (IC3) of the rat tGLP-1R was systemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 0 publications
2
13
1
1
Order By: Relevance
“…These data are consistent with the results of the human m 1 muscarinic receptor (36). In contrast, deletion of the threonine, aspartic acid, and isoleucine (TDI) motif within the central region of the third endoloop of the GLP-1 receptor led to a significant reduction in receptor expression (30). The corresponding mutant in the hSR is IC3-3 with the glycine, asparagine, glutamic acid, valine (GNEV) motif deleted, and this mutant is functionally indistinguishable from the WT receptor.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These data are consistent with the results of the human m 1 muscarinic receptor (36). In contrast, deletion of the threonine, aspartic acid, and isoleucine (TDI) motif within the central region of the third endoloop of the GLP-1 receptor led to a significant reduction in receptor expression (30). The corresponding mutant in the hSR is IC3-3 with the glycine, asparagine, glutamic acid, valine (GNEV) motif deleted, and this mutant is functionally indistinguishable from the WT receptor.…”
Section: Discussionsupporting
confidence: 90%
“…Within the third endoloop, the function of the conserved basic motif at the N-terminal region as the site for G protein interaction has been a focus of interest, and the results obtained are controversial. Evidence supporting this notion can be found in studies of the GLP-1, rhodopsin, and ␤ 2-adrenergic and muscarinic receptors (30,(32)(33)(34). Instead, other reports have suggested that the hydrophobic residues at the junction of the fifth transmembrane domain of GLP-1 receptor (29) and those at the end of the third endoloop of ␤-adrenergic receptor (35) are involved in G protein coupling.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies with the rat GLP-1 receptor demonstrated that the KLK motif, and in particular the first lysine residue, is required for the efficient coupling of the receptor to adenylyl cyclase. Alteration of this motif or the lysine residue in the GLP-1 receptor resulted in significantly reduced cAMP production (59). The KLR motif of the glucagon receptors is found in the same position as the KLK motif of GLP-1 receptors (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Within the third intracellular loop, mutation of a central lysine-leucine motif of the opossum parathyroid hormone receptor, rat GLP1 receptor, and human VPAC1 and VPAC2 receptors, analogous to the human secretin receptor residues Lys 302 -Leu 303 (ICL3A), results in defects in agonist-stimulated cAMP production, calcium mobilization, and ligand binding to varying degrees (1,7,25,38,45,62). In the present work, replacing these residues with alanines in the human secretin receptor resulted in normal ligand binding and calcium signaling, but reduced cAMP responses.…”
Section: Discussionmentioning
confidence: 99%